12.3: Development of Electro‐Osmotic Color E‐paper. Issue 1 (1st July 2013) - Hoehla, Steffen; Henzen, Alex; Fruehauf, Norbert
Abstract: Electronic paper devices based on electrophoretic layers are now predominantly limited to greyscale reproduction of (semi)static information. This has been acceptable in the past, but the near future will require color, with ever more and better colors. The final goal is a color image that challenges the performance of a color photograph. This paper describes the results of a first prototype electro‐osmotic color display capable of achieving this, opening the route to bright, full color displays compatible with existing LCD infrastructure.